Reforming Food and Eating in Protestant England, c. 1560–c. 1640 - Barnett, Eleanor (The historical journal, 2020)
As the field of food history has come to fruition in the last few decades, cultural historians of early modern England have begun to recognize the significance of food and eating practices in the process of identity construction. Yet its effect on religious identities has yet to be written. This article illuminates a printed discourse in which Protestants laboured to define a new relationship to food and eating in light of the Reformation, from Elizabeth I's reign up until the Civil War. It is based on a wealth of religious tracts written by the clergy, alongside the work of physicians in the form of dietaries and regimens, which together highlight the close relationship between bodily and spiritual concerns. As a result of the theological changes of the Reformation, reformers sought to desacralize Catholic notions of holy food. However, by paying greater attention to the body, this article argues that eating continued to be a religiously significant act, which could both threaten spiritual health and enrich it. This discourse on food and eating helped draw the confessional boundaries and identities of the Reformation period, and so offers a rewarding and novel insight into English Protestantism.